The double-edged sword of servitization in radical product innovation: The role of latent needs identification. (December 2022) - Wang, Yanping; Gao, Jie; Wei, Zelong
Abstract: Using survey data from 208 Chinese manufacturing firms, this paper empirically explores whether servitization facilitates or hinders radical product innovation performance. On the basis of organizational knowledge creation theory, we argue that servitization enables manufacturers to identify latent customer needs that are valuable in searching for radical product innovation opportunities. However, according to social structural embeddedness theory, a firm with a high level of servitization becomes overembedded in customer relationships, which prevents it from seizing such opportunities. We integrate these two theories and find an inverted U-shaped relationship between servitization and radical product innovation performance. Our research enriches the servitization literature by identifying and integrating the two roles of servitization for radical product innovation performance. Highlights: Servitization positively relates to radical product innovation through latent needs identification. Servitization has its dark side to radical product innovation by weakening the effect of latent needs identification. Combining both logics, servitization has an inverted U-shaped relationship with radical product innovation performance.